(untitled) (Research, Society and Development, 2020)
Monitoring phenomena that occur in nature, be they natural or man-made, is an important technique to mitigate their negative effects. This study aims to perform the spatio-temporal analysis of the occurrence of hot spots in Santa Helena de Goiás in the years 2015, 2016 and 2017. The cartographic database consisted of municipal limits; spatial data of hot spots for the years 2015, 2016 and 2017; as well as satellite image for the identification of land use and cover. The heat focus data were obtained through the platform of the Institute for Space Research on the electronic page “Bdqueimadas”, the data were acquired in shapefile extension (.shp). These data are generated from images of sensors on board the polar satellites and geostationary satellites, and the heat sources for that study were derived from the processing and integration of daily data from different sensors. During the period there was a 32.60% decrease in occurrences between 2015 and 2016. While between 2016 and 2017 there was a 28.76% increase between the two periods. The total number of occurrences in the period was 2041 hot spots, 38.17% in 2015, 25.72% in 2016 and 36.11% in 2017. The importance of using geoprocessing tools to identify areas with a history of hot spots in the municipality of Santa Helena de Goiás, thus assisting in public measures aimed at reducing and preventing these occurrences so that they have a lower proportion and losses.